2016
DOI: 10.1007/s10964-016-0517-z
|View full text |Cite
|
Sign up to set email alerts
|

Congruence and Incongruence in Adolescents’ and Parents’ Perceptions of the Family: Using Response Surface Analysis to Examine Links with Adolescents’ Psychological Adjustment

Abstract: Parents and adolescents often hold discrepant views about the family environment and these discrepancies may in turn influence adolescents' psychological adjustment. The current study examined how adolescent-parent perceptions of family routines and chaos, and their congruence and incongruence, relate to adolescents' self-reported psychological adjustment (depressive symptoms and perceived stress), both concurrently (N dyads = 261; 53 % female) and 2 years later (N dyads = 118; 50 % female). Using polynomial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 41 publications
9
75
0
1
Order By: Relevance
“…To cite just some examples from the articles in the Special Issue, Nelemans et al (2016) tested discrepancies in parent and adolescent perceptions about their relationship as predictors of adolescent-reported depression; Human et al (2016) focused on family routines and chaos as predictors of adolescent self-reported depression and perceived stress; Jager et al (2016) analyzed adolescents' perceptions of parental rejection as predictors of internalizing and externalizing problems as rated by mothers, fathers, and the adolescents themselves; Borelli et al (2016) used discrepancies in mothers and adolescents' ''we-talk'' in interviews following the child's participation in a standardized failure task as predictors of the adolescent's trait rumination measured before the task and cortisol reactivity following the task, as well as the mother's ''overcontrol'' during the task; Valdes et al (2016) tested maternal and adolescent ratings of maternal psychological control as predictors of adolescent anxiety and conduct problems as rated by both kinds of informant; Leung et al (2016) used reports of family functioning to predict adolescent beliefs in the future, resilience, cognitive competence, self-efficacy, and selfdetermination; and Ohannessian et al (2016) studied how convergence in ratings by mothers and adolescents regarding family communication and satisfaction predicted maternal psychological symptomatology. In short, the articles in this Special Issue address an impressive array of aspects of family functioning and a very diverse set of outcomes associated with these aspects of family functioning.…”
Section: Breadth Of Topics Addressedmentioning
confidence: 99%
See 1 more Smart Citation
“…To cite just some examples from the articles in the Special Issue, Nelemans et al (2016) tested discrepancies in parent and adolescent perceptions about their relationship as predictors of adolescent-reported depression; Human et al (2016) focused on family routines and chaos as predictors of adolescent self-reported depression and perceived stress; Jager et al (2016) analyzed adolescents' perceptions of parental rejection as predictors of internalizing and externalizing problems as rated by mothers, fathers, and the adolescents themselves; Borelli et al (2016) used discrepancies in mothers and adolescents' ''we-talk'' in interviews following the child's participation in a standardized failure task as predictors of the adolescent's trait rumination measured before the task and cortisol reactivity following the task, as well as the mother's ''overcontrol'' during the task; Valdes et al (2016) tested maternal and adolescent ratings of maternal psychological control as predictors of adolescent anxiety and conduct problems as rated by both kinds of informant; Leung et al (2016) used reports of family functioning to predict adolescent beliefs in the future, resilience, cognitive competence, self-efficacy, and selfdetermination; and Ohannessian et al (2016) studied how convergence in ratings by mothers and adolescents regarding family communication and satisfaction predicted maternal psychological symptomatology. In short, the articles in this Special Issue address an impressive array of aspects of family functioning and a very diverse set of outcomes associated with these aspects of family functioning.…”
Section: Breadth Of Topics Addressedmentioning
confidence: 99%
“…For example, Human et al (2016) used response surface analysis (RSA), which uses coefficients from polynomial regression to graphically depict patterns of congruence and incongruence for an independent variable (e.g., family chaos) and an outcome variable (e.g., teen depression). Córdova et al (2016) used longitudinal confirmatory factor analysis (LCFA) to determine if indicators of family functioning on six measures rated by parents and adolescents (focus on family communication, parent-adolescent communication, family cohesion, parental monitoring, parent support, and parent involvement) could be represented by a single latent variable for each kind of informant and if the CFA structure was stable over time.…”
Section: Innovative Statistical Approaches Employedmentioning
confidence: 99%
“…Given that the correlations between the PSES and parent report of adolescent symptoms were already quite low, it is unsurprising that correlations between the PSES and adolescent reports of their own symptoms were not significant. Discrepancies between adolescent and parent reports are not uncommon in parenting research (Bögels & Melick, ; De Los Reyes & Ohannessian, ; Human, Dirks, DeLongis, & Chen, ). However, this is contrary to findings by Steca et al.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the stressor of parental symptoms of psychological problems may have been too mild compared to other studies that examined the relationships between parental clinical depression or anxiety disorders and depression and anxiety symptoms in adolescents (Lieb et al., ). In addition, earlier studies found that children's perceptions of the family environment are adequate and that children are influenced by their perceptions about parental attitudes and behavior, rather than by the actual parental behaviors or the behavior reported by parents (Demo, Small, & Savin‐Williams, ; Human, Dirks, DeLongis, & Chen, ; Tein, Roosa, & Michaels, ). In this study, parents reported about their own psychopathology, and that might have contributed to not finding a relationship, especially because levels of parental psychopathology were low.…”
Section: Discussionmentioning
confidence: 99%